Tourists’ emotions as a resource for customer value creation, cocreation, and destruction: a customer-grounded understanding - Malone, Sheila; McKechnie, Sally; Tynan, Caroline (SAGE, 2017)
Research on customer value creation in a tourism setting has tended to prioritize the firm’s over the customer’s perspective. However, new understandings of customer value through the lens of customer-dominant logic emphasize the need to consider value as emerging within the broader context of a customer’s lifeworld, which transcends customer–firm interactions and includes interactions with others. Tourism experiences are experiential and meaning-laden at the individual and collective levels. As a resource for value creation, emotions play an important but underexplored role during value-in-use and influence the tourist’s consumption experience. We provide a customer-grounded understanding of value creation as emerging and evolving over time by examining how emotions are experienced and contribute to the holistic consumption experience both intra- and intersubjectively. By demonstrating how emotions, as a customer operant resource, contribute to the process of value creation as well as value destruction, we extend our knowledge of experiential consumption practices.